The Arts Club anthology : 50 years of Canadian theatre in Vancouver - Ditor, Rachel; Arts Club Theatre Company (Toronto : Playwrights Canada Press, 2014)
In time for the Arts Club Theatre Company's fiftieth anniversary, this anthology collects six of the most cherished and popular plays that have captivated audiences for the past five decades.
Keywords: Arts Club Theatre Company -- Anniversaries, etc; Canadian drama (English) -- British Columbia -- Vancouver; Canadian drama (English) -- 20th century; Canadian drama (English) -- 21st century; Anniversaries; Canadian drama; British Columbia -- Vancouver; 1900-2099; Drama